Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12889-017-4137-7
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete childhood immunization in Nigeria: a multilevel analysis of individual and contextual factors

Abstract: BackgroundUnder-five mortality remains high in sub-Saharan Africa despite global decline. One quarter of these deaths are preventable through interventions such as immunization. The aim of this study was to examine the independent effects of individual-, community- and state-level factors on incomplete childhood immunization in Nigeria, which is one of the 10 countries where most of the incompletely immunised children in the world live.MethodsThe study was based on secondary analyses of cross-sectional data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
199
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(251 citation statements)
references
References 27 publications
44
199
5
3
Order By: Relevance
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used cross-sectional design [1-3, 11, 13-17, 19, 21-26, 28-36, 38-39, 42, 45-46, 48-51, 53, 54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used cross-sectional design [1-3, 11, 13-17, 19, 21-26, 28-36, 38-39, 42, 45-46, 48-51, 53, 54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
“…The older women, having cared for many children, are likely to know the importance of immunization. 21,22 This study shows that education plays a major role in improving vaccination coverage. The probability of a child of an HIV positive mother not taking DTP3 is reduced in women with any form of formal education compared to their uneducated counterparts.…”
Section: Discussionmentioning
confidence: 75%
“…19,20 Unemployment leads to poverty, and studies have shown that the more the poverty level of a household, the more likely it is that its children would be incompletely vaccinated. 21 Lack of basic resources leads to poor health seeking behaviour and deprivation of required immunization, and subsequently being exposed to vaccine-preventable diseases. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations